2022
DOI: 10.1007/s10551-022-05179-x
|View full text |Cite
|
Sign up to set email alerts
|

Three Paths to Feeling Just: How Managers Grapple with Justice Conundrums During Organizational Change

Abstract: Managers tasked with organizational change often face irreconcilable demands on how to enact justice—situations we call justice conundrums. Drawing on interviews held with managers before and after a planned large-scale change, we identify specific conundrums and illustrate how managers grapple with these through three prototypical paths. Among our participants, the paths increasingly diverged over time, culminating in distinct career decisions. Based on our findings, we develop an integrative process model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…While the examination of recipients' and observers' perspectives has borne considerable fruit, only a handful of studies have considered the deontic perspective of managers (for a review, see Graso et al, 2019). Previous research, however, has indicated that justice enactment can also be "a matter of moral imperative" (Qin et al, 2018;Zwank et al, 2022) and attributed managers' interest in fair treatment to the character of the actor, such as caring for others or moral obligation (Brebels et al, 2011;Patient & Skarlicki, 2010). In their actor-focused model of justice enactment, Scott et al (2009) recognized that actors may adhere to justice rules due to their cognitive compliance motive or positive affective motive, which promote prosocial behaviors, or may violate these rules to rectify what they perceive as employee wrongdoing.…”
Section: Justice Enactment As Deonancementioning
confidence: 99%
See 3 more Smart Citations
“…While the examination of recipients' and observers' perspectives has borne considerable fruit, only a handful of studies have considered the deontic perspective of managers (for a review, see Graso et al, 2019). Previous research, however, has indicated that justice enactment can also be "a matter of moral imperative" (Qin et al, 2018;Zwank et al, 2022) and attributed managers' interest in fair treatment to the character of the actor, such as caring for others or moral obligation (Brebels et al, 2011;Patient & Skarlicki, 2010). In their actor-focused model of justice enactment, Scott et al (2009) recognized that actors may adhere to justice rules due to their cognitive compliance motive or positive affective motive, which promote prosocial behaviors, or may violate these rules to rectify what they perceive as employee wrongdoing.…”
Section: Justice Enactment As Deonancementioning
confidence: 99%
“…The literature indicates that in areas where the self is less "invested" (Hannah et al, 2011a), individuals who are low in moral maturation-whom we may also call "weak persons"-are more susceptible to contextual influences. Especially in times of difficult organizational changes, when managers are forced to make and implement tough decisions-such as layoffs or contract terminations caused by cost-cutting plans or efficiency programs-the gap between an individual's deontic justice motive and subsequent behavior is likely to widen, and strong situational pressures may easily override an actor's fairness intentions (Camps et al, 2022;Jennings et al, 2015;Jordan et al, 2011;Zwank et al, 2022). In contrast, a "strong," highly morally mature person-a more complex person with greater metacognitive ability and moral identity-can draw from a broader base of moral content and better tailor and consciously direct their active self across a broad range of situations (Hannah et al 2009(Hannah et al , 2011aLord et al, 2011).…”
Section: Intraindividual Variability and Consistency In Deontic Justi...mentioning
confidence: 99%
See 2 more Smart Citations
“…First, we distinguish between mitigative practices, which enable workers to carry out tasks in a way that is less harmful than would otherwise be the case, and transformative practices, which are performed after a task to make up for the harm endured by the target. Previously contemplated responses to harm-doing, such as leaving the organization, emotionally disengaging, or blaming targets (Andiappan and Dufour, 2017;Zwank et al, 2023) are primarily destructive. Remediation practices, by contrast, are both proactive and constructive, appearing to benefit targets and performers of harm.…”
Section: Theoretical Contributionsmentioning
confidence: 99%